PENGARUH PENERAPAN ANGGRARAN BERBASIS KINERJA, SISTEM INFORMASI PENGELOLAAN KEUANGAN DAERAH DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP KINERJA SKPD PROVINSI RIAU (Studi Empiris Pada SKPD Provinsi Riau) - Rinda Permata Sari; Kennedy -; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aims to prove the effect of Application of Performance-Based Budgeting to performance SKPD Riau province, then Effect of System of Financial Management Information on the performance of skpd Riau province, and the Effect of Quality of Human Resources to performance SKPD Riau province. The population in this study is the Regional Working Units (on education) in the Riau provincial government on education in 38 provinces comprising Region 1 Secretariat Riau, Riau Province Inspectorate 1, 1 Secretary DPRD Riau, Riau KORPRI 1 Secretary, Civil Service Police Unit 1, 2 Hospital (Hospital and RSJ), Agency 14, and 17 Department. Samples from this study are echelon III and IV at Department and Agency of Riau Province by 86 people. Analysis of the data in this study using tools SPSS software version 17. The results showed that the Application of Performanced-Based Budgeting, System of Financial Management Information, and Quality of Human Resource affect the Performance SKPD Riau province.Keywords: Performanced-Based Budgeting, financial, System of Financial Information area, Performanced and Human Resource to Performanced.